Revisión sistemática del Inventario de Personalidad NEO (NEO-PI) (2011)
ABSTRACT: This paper seeks to establish the applicability of the NEO Personality Inventory (NEO-PI). To this end, a systematic literature review which found 21 articles that met the inclusion criteria of research in 2000-2010. Is a constant use of the instrument, where there is strong evidence of its use, both to investigate personality traits in different populations such as the psychometric properties of the test. It discusses the use made of the evidence and its various factors, it is also recommended to extend the period of time for inclusion of articles.